Sticky ethics: Environmental activism and the limits of ethical freedom in Kerala, India. (September 2020) - Mathias, John
Environmental activists in Kerala, India, often contest the boundaries between the ethical and the non-ethical, flouting widely-accepted norms while ethicalizing usually trivial aspects of everyday life. The resulting ambiguity presents an opportunity to explore a problem that has troubled the recent ethical turn in anthropology: how do we know ethics when we see it? Analyzing seemingly ethicalizing moves during an environmental awareness campaign, I show how ambiguous evaluations can become persistent demands to account for one's actions, even for those who protest, transgress, mock, or otherwise resist them. This process sheds light on the limits of freedom in ethical life and, thus, contributes to debates on how to define ethics for the purposes of anthropological research.